Berkomunikasi Melalui Seni Hadrah (Seni Hadrah sebagai Media Dakwah di Sekolah Menengah Pertama Terpadu Ainul Ulum Pulung Ponorogo) - Yasluh, Muhammad Sholukha; Setyawan, Agus; Muchlis, Ibnu (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2024)
media for communication not only electronic media, hadrah can also be used to communicate through prayer. Communicating through hadrah art is interacting with mad'u or listeners, by chanting sholawat. This research is a field research (field research) which is descriptive qualitative. Data collection techniques were carried out by interviews, observation, and documentation then the collected data were analyzed using inductive thinking methods. Based on the results of data analysis, it was concluded that in 1) Communicating through hadrah art there is a spiritual value including the love of students for the prophet Muhammad Saw, 2) The message of da'wah varies in each poem that is delivered. 3) Bersholawat as a form of realization of obedience to Allah's commands, as well as to obtain intercession from the Prophet Muhammad, 4) Supporting factors, namely: the equipment has been facilitated by the madrasah and the cohesiveness of the players. 5) the inhibiting factors are equipment damage, lack of hadrah trainers and unfavorable weather or rain.